The Evolving Role of the Central Bank of Sri Lanka towards Achieving Economic Stability and Growth: A Critical Legal Analysis - Nanayakkara, P.K.M. (University of Colombo, 2024)
This research critically examines the transformation of the Central Bank of Sri Lanka (CBSL) and its profound impact on the nation’s economic stability and growth. As a result of the Central Bank of Sri Lanka Act No. 16 of 2023, the CBSL has undergone a paradigm shift concerning its objectives, roles, and functions. The new mandate introduced through these provisions, including lucrative and developed provisions, has opened avenues for inclusive considerations of the monetary policy of Sri Lanka, the stability of the economic growth, the sustainability of state and non-state financing sectors, and the inflation control aspects at both macro and micro levels. In this context, this research delves deep into the implications of these changes, shedding light on the new emphasis on price stability within an inflation-targeting framework. This research further explores how the CBSL effectively manages the payment system, undertakes agency functions such as public debt management, and acts as the custodian of the Employees Provident Fund. It highlights the pivotal functions of the CBSL, including the formulation and implementation of monetary policy, currency issuance, and the maintenance of financial stability. Moreover, it explores CBSL’s crucial role as the lender of last resort during financial crises and its active involvement in the regulation and supervision of banks and financial institutions. The research also sheds light on the CBSL’s role in managing...
Keywords: Central Bank of Sri Lanka; Economic Growth; Financial Stability; Monetary Policy